Dynamic monopsony: evidence from a French establishment panel - Fathi Fakhfakh; Felix R. FitzRoy (Institute for the Study of Labor (IZA), 2005)
This paper uses a panel of about 6000 French establishments to test some implications of the modern theory of dynamic monopsony or upward sloping labour supply curves for average firm wages. Panel estimates provide strong evidence of a much larger long run employer size - wage effect (ESWE) than found previously, while controlling for worker quality and compensating differentials with lagged wages, and for profitability (rent sharing). Employment expansion also has a positive effect on wages, providing further evidence for upward sloping labour supply (as distinct from the effect of shocks in a perfectly competitive labour market).
Keywords: C23; J30; J31; 330; labour supply; dynamic monopsony; firm-size wage effect; Monopson; Arbeitsangebot; Betriebsgröße; Lohn; Panel; Frankreich